2007
DOI: 10.1007/s10815-007-9159-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a combined protocol of urinary and recombinant follicle-stimulating hormone used for ovarian stimulation of patients undergoing ICSI cycle

Abstract: Purpose To evaluate the efficacy of using both urinary and recombinant FSH in a combined protocol for ovarian stimulation in an IVF treatment program. Method A total of 119 infertile couples undergoing ICSI treatment were randomized prospectively in this study. After a standard down-regulation with GnRH analogue, the patients were randomized in 2 groups 58 received combined urinary and recombinant FSH, starting with uFSH and then rFSH, and 61 controls received only recombinant FSH. Result(s) Pregnancy and impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 52 publications
5
6
0
Order By: Relevance
“…The miscarriage rates were also similar in all groups. These results support previous studies which have demonstrated that stimulation with the sequential protocol is highly efficacious in terms of oocyte quality, embryo quality, and pregnancy and implantation rates compared with stimulation with less-acidic recombinant FSH alone (47,48).…”
Section: Discussionsupporting
confidence: 91%
“…The miscarriage rates were also similar in all groups. These results support previous studies which have demonstrated that stimulation with the sequential protocol is highly efficacious in terms of oocyte quality, embryo quality, and pregnancy and implantation rates compared with stimulation with less-acidic recombinant FSH alone (47,48).…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that this strategy led to a trend towards a higher, even if not significant pregnancy rate, as mentioned earlier [26][27][28]. The use of hFSH yields the same results as the use of recombinant FSH, in agreement with several other authors [26,27].…”
Section: Discussionsupporting
confidence: 92%
“…Studies have carefully compared treatment characteristics and outcomes in patients treated with different medications (16)(17)(18)(19). Urinary hMG contains 75 IU FSH and 75 IU LH, whereas recombinant FSH is completely free from any LH.…”
mentioning
confidence: 99%